Needs versus wants: comparing job-related and personal needs of non-academic university employees for English language training - Chan, Mei Yuit; Lee, Geok Imm (Universiti Putra Malaysia Press, 2009)
In company-sponsored workplace training programmes, training developers have traditionally focused on employees' job-related needs when designing the training curriculum, in line with conventional wisdom in the practice of human resource development. The personal needs of employees that are not directly related to job demands, commonly labelled as 'wants', are often not considered as important. In the realm of English language learning, however, research and theories have pointed to the importance of learner factors and their motivation for language learning. The sources of motivation, in particular integrative motivation (Gardner and Lambert, 1972), that arise from the learners' personal lives should not be neglected. This study compares the job-related and personal ESL (English as a second language) training needs of a group of non-academic employees of a public university in Malaysia. It investigates the extent to which personal needs are important motivators as compared to job-related needs in workplace English language learning. The framework of this research on workplace learning is informed by theories and concepts developed in the fields of motivation (Gardner and Lambert, 1972; Dornyei, 2005) and domains of language use (Fishman, 1972), as well as workplace training literature (Kraiger and Aguinis, 2001 ; Machin and Treolar, 2004; Tsai and Tai, 2003 ). Data were collected through a questionnaire containing statements of personal and job-related needs. The needs were rank-ordered to identify the most important needs. The results showed that on the whole, the employees found both personal and job-related needs equally relevant. However, analysis of the most important needs indicated a clear preference for personal needs. The results have implications for both the design and instruction of workplace ESL programmes for the study's population, and challenge the common practice of focusing only on job-related language needs in workplace ESL programmes. Finally, the results provide empirical support for the conceptualisation of an L2 workplace training motivation model which takes into consideration personal needs as an important component.